Upaya Menanggulangi Kekerasan dalam Rumah Tangga - Zikri, Ahmad Khairullah; Firmansyah, Wahyu; Ramadhan, M. Irham; Aulia, Shifa; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Domestic violence (DV) is a complex problem that includes legal, social, and cultural aspects. Although it has been regulated in Law No. 23 of 2004 concerning the Elimination of Domestic Violence, this phenomenon remains high, especially against women. This article aims to analyze efforts to overcome domestic violence through a positive legal approach, socio-religious development, and Islamic values, especially the concept of mu'āsyarah bil ma'rūf. The method used is a literature study by reviewing literature from scientific journals, laws and regulations, and the perspectives of Islamic figures and teachings. The results of the study indicate that a repressive approach through law alone is not effective enough without being supported by healthy relationship education, strengthening the role of society, and equal understanding of the rights and obligations of husband and wife. An integrative approach involving education on harmonious families, provision of victim protection, and internalization of the value of justice in the household is a strategic step in reducing the number of domestic violence in Indonesia.